Repartition et quantite d’algues rouges du genre phyllophora sur la plate forme continentale roumaine de la Mer Noire - Vasiliu, Florian; Bodeanu, Nicolae (Cercetări Marine - Recherches Marines, 2026)
The paper presents quantitative data concerning the distribution of red algae Phyllophora species on the continental shelf off the Rumanian coasts. Two species were Identified: Phyllophora nervosa and Phyllophora hrodlaet. These algae are present between 10 to 56m depth, covering a bottom surface of 2,800km2 and having a wet biomass of 7,976tons. Highest biomasses reaching 60 g/m2 were registered on the northern extremity at the considered area, between 43 to 48m depth.